2011
DOI: 10.1007/s11307-011-0481-7
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Imaging of Pancreatic Beta Cells using a Radiolabeled GLP-1 Receptor Agonist

Abstract: Ex vivo autoradiography results using [⁶⁴Cu](Lys⁴⁰(DOTA)NH₂)Exendin-4 suggest that GLP-1R agonists based on Exendin-4 are attractive PET ligands for the in vivo determination of β-cell mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Because native GLP-1 is degraded rapidly by dipeptidyl peptidase IV, a more stable agonist of GLP-1 (such as exendin-4) is a preferred imaging agent. Previously, exendin-4 was radiolabeled with long-lived nuclides, such as 111 In (5,6) and 64 Cu (7,8), for use in SPECT and PET. These analogs have shown promise for imaging of tumors of b-cell origin (insulinomas) as well as transplanted islets (9).…”
mentioning
confidence: 99%
“…Because native GLP-1 is degraded rapidly by dipeptidyl peptidase IV, a more stable agonist of GLP-1 (such as exendin-4) is a preferred imaging agent. Previously, exendin-4 was radiolabeled with long-lived nuclides, such as 111 In (5,6) and 64 Cu (7,8), for use in SPECT and PET. These analogs have shown promise for imaging of tumors of b-cell origin (insulinomas) as well as transplanted islets (9).…”
mentioning
confidence: 99%
“…Exendin-4 displays biologic properties similar to human GLP-1, with which it shares 53% sequence identity (13); however, it is much more stable metabolically than GLP-1. Previously, exendin analogs have been radiolabeled and evaluated for islet imaging in rodents (14,15) and humans (16). Although these tracers showed great potential for islet imaging, there are 2 major challenges for these probes: first, the high and persistent kidney accumulation of the radiometal-labeled probes may limit their clinical translation because of radiation exposure; second, a probe with high specific activity is needed to avoid blocking effects, as the receptor number is limited.…”
mentioning
confidence: 99%
“…Communication with the pathologist ahead of time is recommended to facilitate prompt analysis. Frozen section has been shown to be a very reliable method for the characterization of testicular masses with high specificity and sensitivity in multiple studies, and to distinguish benign from malignant masses [62][63][64][65]. Likewise, Connolly et al [66] reported a 94.2% positive predictive value and 92.6% negative predictive value for malignancy in a series of 80 patients.…”
Section: Operative Techniquementioning
confidence: 99%